Evaluacion comparativa de dos tipos de muestreo en chucheca (Grandiarca grandis) y piangua (Anadara tuberculosa), en el Golfo de Nicoya, Costa Rica (ING) - Bolaños Montero, Juan (1996)
A comparative study was carried out in order to test the statistic goodness of two sampling methods, working with mollusks in the mangrove ecosystem. Stratified random sampling proved to be better than unrestrained random sampling.